PENILAIAN SAHAM PT. SEJAHTERARAYA ANUGRAHJAYA TBK. DALAM RANGKA INVESTASI OLEH PT. NIRMALA KENCANA MAS UNTUK PEMBANGUNAN MAYAPADA HOSPITAL - , Miduk Pakpahan, S.E. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to estimate the intrinsic value of the shares of PT. Sejahteraraya Anugrahjaya Tbk. relating to the investment of a subsidiary PT. Nirmala Kencana Mas. The intrinsic value of the shares of PT. Sejahteraraya Anugrahjaya Tbk. counted by using the income approach is to apply the discounted cash flow method in 2 (two) scenarios that are, with scenario the investment of a subsidiary not go and with scenario investment of a subsidiary go. The market data comparison approach (relative valuation) is applied as a sanitary chek. The data used consists of financial statements data PT. Sejahteraraya Anugrahjaya Tbk during the last five years from 2007 to 2011 and business plan from 2012 to 2021. Analysis of discounted cash flow method conducted by: an analysis of financial projections, the projected free cash flow, the determination of the discount rate or the level of feed back is expected and the estimated value. Analysis of the market data comparison approach (relative valuation) begins with finding comparable companies in similar lines of business subsequent to choose and assign the appropriate multiples or ratios of comparable companies. Multiples are used to convert the book value of relevant variables from the PT. Sejahteraraya Anugrahjaya Tbk be the estimated market value. Multiplesor ratios used are: PBV (Price to Book Value), P / S (Price to Sales Ratio), and Price/EBITDA. The results of the income approach by applying the discounted cash flow method, with scenario the investment of subsidiary (the development of Mayapada Hospital) not go, obtained estimates of the intrinsic value of the shares of PT. Sejahteraraya Anugrahjaya Tbk. as of December 2011 amount to Rp200,-per share, whereas with scenario the investment of subsidiary (the development of Mayapada Hospital) go, obtained estimates of the intrinsic value of the shares of PT. Sejahteraraya Anugrahjaya Tbk. as of December 2011 amount to Rp375,-per share. The results of the market data comparison approach (relative valuation), obtained estimates of the intrinsic value of the shares of PT. Sejahteraraya Anugrahjaya Tbk. as of December 2011 amount to Rp201,-per share. Value of the shares of PT. Sejahteraraya Anugrahjaya Tbk and financial ratios with scenario the investment of subsidiary go, increased when compared to the value of financial ratios with scenario the investment of subsidiary not go, so with scenario the investment of subsidiary go is the right choice by management and safe for the shareholders